Variability in speaker expectations of morphosyntactic mutation in Welsh - White, Yosiane; Roberts, Gareth (Glossa (London), 2022)
Like all modern Celtic languages Welsh exhibits initial consonant mutation with both lexical and morphosyntactic triggers. Owing to the complexity of the system and the sociolinguistic situation of Welsh, change and variation in the system seems inevitable, and evidence for change has been observed in production. Less work, however, has focused on speakers’ attitudes and expectations in perception. We used an online auditory acceptability judgement survey to investigate expectations for different morphosyntactic soft-mutation triggers. Respondents listened to sentences with canonical and non-canonical mutation patterns and used Likert scales to indicate for each sentence whether they would use the same pattern themselves and whether they would expect it from others. Almost all respondents expected some variation, even in their own production, but two main clusters of respondents could be identified: “Conservative” respondents whose expectations were close to canonical mutation patterns and “Variable” respondents whose expectations were considerably more flexible. First-language status was the only demographic variable to predict respondent attitudes, suggesting that L2 Welsh speakers accept noncanonical mutation to a greater extent than L1 Welsh speakers. We also compared different mutation triggers, with the tentative conclusion that apparently identical triggers may not in fact be identical for all speakers, and that trigger transparency may be an important factor in predicting variability.